Impact of Nutrition Education on Knowledge of Rural Women - Anuradha Ranjan Kumari , Basanti Kumari and Laxmikant, (Indian Journal of Extension Education, 2015)
Nutrition Education is any combination of educational strategies, accompanied by environmental supports, designed tofacilitate voluntary adoption of food choices and other food and nutrition related behaviors conducive to health and wellbeing. Nutrition education is delivered through multiple venues and involves activities at the individual, community, andpolicy levels. A longitudinal study indicated the impact of nutrition education on rural women of Salempur block ofDeoria district. Aspecial nutrition training programme revealed that nutrition education affected an increase in knowledgegain, the motivation of women improvement reflected in the selection of food, cooking practices with increase in nutritivevalue of food. The most significant improvement was observed in the fuel consumption pattern, balanced diet andconservation of nutrients. It was observed that rural women motivated and guided efficiently. It would definitely fasterdesirable change in them which ultimately results in bringing improvement in the nutritional status of community as awhole.